Family support and family and child-related outcomes among families impacted by disability in low- and middle-income countries: A scoping review. (24th October 2019) - Nuri, Reshma Parvin; Batorowicz, Beata; Aldersey, Heather Michelle
There is a growing interest in understanding the relationship between family support and family or child-related outcomes in high-income countries. However, this has received little attention in low- and middle-income countries. The purpose of this review was to explore the relationship between family support and family and child-related outcomes among families affected by disability in low- and middle-income countries. We conducted a scoping review of five databases using search terms related to 'family', 'support', 'child', and 'disability'. A total of 13 articles met the inclusion criteria. Families of children with disabilities received most of their support from informal sources (e.g. immediate family members, friends, and parents support groups). Parental stress was most often evaluated as the family outcome and was negatively linked to emotional support and childcare assistance from immediate family members. Movement and mobility therapy offered by rehabilitation professionals was found to improve children's walking patterns. Positive attitudes from community members were key facilitators to participation of children with disabilities in social activities. The review calls for urgent attention to research in low- and middle-income countries, particularly the extent of support families are receiving from government-led support systems.